Chair of sustainable development. - DI CASTRI, Francesco (1995)
Notes that as an umbrella concept, sustainable development has many dimensions. At an operational level, four interlinked dimensions can be recognised - economic, environmental, social and cultural - and there needs to be a balance between those four dimensions for development to be sustained in the long run. In steering towards such a goal, advantage should be taken of the positive aspects of diversity and globalization.